1993
DOI: 10.1177/0146167293192002
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Context, and Expression of Positive Emotion

Abstract: This study investigated whether positive emotion is differentially prescribed for men and women in self-and other-oriented contexts. Subjects read a scene in which the main character either did or did not express positive emotion toward either the self or another person. After imagining themselves as the main character, subjects rated on a rewards/costs scale how others would respond to them if they had behaved as depicted. Females expected more rewards/fewer costs when positive emotion was expressed toward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 15 publications
4
39
0
3
Order By: Relevance
“…A similar perspective underlies Averill's (1997) argument regarding the notion of emotion roles that have entrance requirements such that, for example, a successful display of anger presupposes sufficient power to adequately address the anger eliciting issue. Also, Stoppard and Gruchy (1993) found that individuals anticipate costs and rewards for showing certain emotions in certain contexts. Specifically, women expect more costs when not expressing positive emotions in an ''other''-oriented context, whereas men expect rewards for showing positive emotions regardless of context.…”
Section: Discussionmentioning
confidence: 99%
“…A similar perspective underlies Averill's (1997) argument regarding the notion of emotion roles that have entrance requirements such that, for example, a successful display of anger presupposes sufficient power to adequately address the anger eliciting issue. Also, Stoppard and Gruchy (1993) found that individuals anticipate costs and rewards for showing certain emotions in certain contexts. Specifically, women expect more costs when not expressing positive emotions in an ''other''-oriented context, whereas men expect rewards for showing positive emotions regardless of context.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in crying, smiling and aggressive behavior therefore seem partly based on gender-specific display rules. Many sex differences are context-dependent, and socialized in accordance with display rules, prescriptive social norms that dictate how, when and where emotions can be expressed by males and females (Brody & Hall, 1993;Fischer, 1993;Fischer, Rodriguez Mosquera, van Vianen, & Manstead, 2004;Shields, 1987;Stoppard & Gruchy, 1993;Underwood, Coie, & Herbsman, 1992). We will elaborate on this issue in the next section.…”
Section: Are Women More Emotional Than Men?mentioning
confidence: 99%
“…In contrast, women's most important values were trying to understand and improve their relationships, be tolerant, and act in a benevolent manner toward other people (Schwartz & Rubel, 2005). Due to deeply ingrained social norms or self-selected values, women focus greater efforts on regulating interpersonal relationships, whereas men focus their emotional expression on the maintenance and pursuit of power and status (Brody, 1997(Brody, , 1999Stoppard & Gruchy, 1993).…”
Section: Gender Differences In Emotionsmentioning
confidence: 99%